Odpowiedzi

2010-03-24T22:39:49+01:00
2-½(4x+6) =5x-1
2-2x-3=5x-1
-2x-5x=-1-2+3
-7x=0
x=0

d)

2-½(4*3+6) =5*3-1
2-1/2*18=14
-7=14

2-½(4*2+6) =5*2-1
2-1/2*14=9
-5=9

2-½(4*1+6) =5*1-1
2-1/2*10=4
-3=4

2-½(4*0+6) =5*0-1
2-1/2*6=-1
-1=-1
Najlepsza Odpowiedź!
2010-03-24T22:43:04+01:00
2-½(4x+6)=5x-1
2-2x-3=5x-1
-2x-5x=-1-2+3
-7x=0
x=0

czyli odp. d jest dobra

spr. a]
x=3
2-½(4×3+6)=5×3-1
2-9=14
-7≠14

b]
x=2
2-½(4×2+6)=5×2-1
2-7=9
-5≠9
c]x=1
2-½(4+6)=5-1
2-5=4
-3≠4
d]x=0
2-½(4×0+6)=5×0-1
2-3=-1
-1=-1
2010-03-24T22:44:53+01:00
2-½(4x+6) =5x-1
a) 3
b)2
c )1
d)0

a)
2 - 1/2(4 * 3 + 6) = 5 * 3 - 1
2 - 1/2(12 + 6) = 15 - 1
2 - 1/2 * 18 = 14
2 - 9 = 14
-7 ≠ 14

b)
2 - 1/2(4 * 2 + 6) = 5 * 2 - 1
2 - 1/2(8 + 6) = 10 - 1
2 - 1/2 * 14 = 9
2 - 7 = 9
-5 ≠ 9

c)
2 - 1/2(4 * 1 + 6) = 5 * 1 - 1
2 - 1/2(4 + 6) = 5 - 1
2 - 1/2 * 10 = 4
2 - 5 = 4
-3 ≠ 4

d)
2 - 1/2(4 * 0 + 6) = 5 * 0 - 1
2 - 1/2(0 + 6) = 0 - 1
2 - 1/2 * 6 = -1
2 - 3 = -1
-1 = -1